Optical properties of hair and their role in precise coloring: application of the chromalens algorithm for color adaptation to different types of lighting - Semen, Olha (Global Prosperity, 2025)
Abstract. This article examines the modern understanding of the optical behavior of the hair fiber and its relevance for professional hair coloring, particularly under variable and multi-source lighting conditions. With the growing use of LED systems, studio lighting, and runway illumination, hair color has become increasingly unstable to the eye, even when the pigment formula itself is technically accurate. Based on current scientific evidence, the paper explains how the condition of the cuticle, the degree of porosity, pigment depth, and internal light scattering shape the final visual appearance of color. Special attention is given to the fact that hair is not an optically uniform structure: different micro-zones of the same strand may react differently to studio, natural, stage, and LED lighting, resulting in uneven tone perception. In this context, the article positions the ChromaLens Precision Mapping methodology as an engineering-based approach to predictive coloring. ChromaLens Precision Mapping integrates optical diagnostics, photometric parameters, pigment-depth analysis, and formula adaptation for specific lighting scenarios. This makes it possible to minimize unwanted tonal shifts, increase color stability, and maintain three-dimensional visual depth even in motion. This is especially important for the fashion industry, runway shows, and professional photo shoots. The paper also outlines key directions for future research, including more precise modeling of hair’s micro-optical zones, the development of standardized predictive algorithms, and the creation of digital tools capable of accounting for the individual optical properties of the hair fiber. Overall, the presented material provides a scientific foundation for advancing color technologies and improving professional practice within the beauty and fashion domains.